Pendampingan Pembiasaan Shalat Ashar Berjamaah Sebagai Penguatan Karakter Siswa X MPK 1 Di SMK Negeri 2 Palangka Raya - Masitah; Muslimah; Sari Kartini (CV. Multi Kreasi Media, 2024)
This article discusses assistance in implementing the Asr prayer habit in congregation at SMK Negeri 2 Palangka Raya, which is aimed at increasing students' awareness and participation in carrying out prayers. This activity was carried out for 16 weeks involving class X MPK 1 students as service subjects. This service uses a participatory and collaborative approach, involving Islamic Religious Education students and teachers. The results of the service showed that students' attendance at congregational Asr prayers increased significantly, reaching 100% at the end of the activity. Apart from that, this activity also contributes to the formation of positive character, discipline and responsibility among students. It is hoped that this initiative can become a model for other schools in building student character and spirituality in the era of globalization.